Kurikulum Merdeka Workshop Implementasi Kurikulum Merdeka dan Pemanfaatan Platform Canva - Helmi Auliya; Angga Sofyana Widyatama; Lailatur Mahfiroh; Ainur Rohmatul Lutsiatus S; Dinik Trisiana Siti Maskhanah; Siti Listiyowati; Almira Nurfi Hafizah; Prasetyo Listiaji (Informa Science, 2023)
Kurikulum Merdeka is a new policy in the Kemendikbud Republik Indonesia which demands a change in learning approaches that are more contextual, innovative and creative. However, the implementation of the Independent Curriculum is currently still facing various obstacles, especially related to limited facilities and infrastructure and limited teacher skills in developing and delivering learning materials. Therefore, this study aims to provide solutions to overcome these obstacles by utilizing the Canva platform as an innovative and easy-to-use learning medium. This study uses the method of developing skills (soft skills) which involves the teacher as the main user. The results of this study indicate that using the Canva platform can increase teacher creativity and ability to develop learning materials, prepare learning tools, and facilitate the process of delivering material to students so that the expected learning outcomes can be achieved and learning can be of higher quality. This program was held on 25-26 February 2023 at MTs. Muhammad Nalumsari. The results of the activity show that there is an increase in teacher skills in using Canva and in making learning designs.